The efficiency of the translesion synthesis across abasic sites by mitochondrial DNA polymerase is low in mitochondria of 3T3 cells. (1st November 2016) - Kozhukhar, Natalya; Spadafora, Domenico; Fayzulin, Rafik; Shokolenko, Inna N.; Alexeyev, Mikhail
Abstract: Translesion synthesis by specialized DNA polymerases is an important strategy for mitigating DNA damage that cannot be otherwise repaired either due to the chemical nature of the lesion. Apurinic/Apyrimidinic (abasic, AP) sites represent a block to both transcription and replication, and are normally repaired by the base excision repair (BER) pathway. However, when the number of abasic sites exceeds BER capacity, mitochondrial DNA is targeted for degradation. Here, we used two uracil- N -glycosylase (UNG1) mutants, Y147A or N204D, to generate AP sites directly in the mtDNA of NIH3T3 cells in vivo at sites normally occupied by T or C residues, respectively, and to study repair of these lesions in their native context. We conclude that mitochondrial DNA polymerase γ (Pol γ) is capable of translesion synthesis across AP sites in mitochondria of the NIH3T3 cells, and obeys the A-rule. However, in our system, base excision repair (BER) and mtDNA degradation occur more frequently than translesion bypass of AP sites.